Intervensi Mindful Breathing Untuk Mengatasi Stres Akademik Pada Remaja Sekolah Menengah Atas - Primalita Putri Distina (Department of Islamic Psychology, Institut Agama Islam Negeri Syaikh Abdurrahman Siddik Bangka Belitung, 2021)
High school students are prone in experiencing academic stress. Academic stressors faced are in the form of pressure to have a lot of assignments, length of study, poor time management, to anxiety facing exams. Some research shows that academic stress of high school students are in the high category. In an extreme case, academic stress can lead to self-harm behavior. One of the interventions that can overcome academic stress is mindful breathing. This study aims to determine the result of mindful breathing intervention to overcome academic stress in high school students. This study used a single-subject design, with one subject aged 16 years who was in grade XI. The flow of intervention consists of counseling sessions, preparation, implementation of the intervention, and evaluation. The results showed that the mindful breathing intervention was successful in dealing with academic stress in high school students.